Dynamic Rehabilitation of Facial Nerve Injury: A Review of the Literature - Rabie, Amr N.; Ibrahim, Ahmed M. S.; Kim, Peter S.; Medina, Miguel; Upton, Joseph; Lee, Bernard T.; Lin, Samuel J. (Journal of Reconstructive Microsurgery, 2013)
Introduction Given the morbidity caused by facial nerve paralysis, there have been consistent approaches to treatment over the past 20 years in reanimation of the facial nerve. Treatment depends on accurate clinical examination, a good understanding of the anatomic course, and appropriate diagnostic tests. There are various options when it comes to dynamic facial nerve reanimation that range from nerve grafting, nerve anastomosis, crossover techniques and muscle transfer to microneurovascular muscle flaps, and—recently—potentially new concepts with microelectromechanical systems (MEMS) technology. The various dynamic facial nerve treatment modalities are discussed. Methods and Results A comprehensive review of the literature was performed detailing various techniques used for dynamic rehabilitation following facial nerve injury and their known results and complications. Conclusions Currently, techniques have been attempted to achieve adequate dynamic facial reanimation of the paralyzed facial nerve. Despite the advances that have occurred in the last few years, it has been classically very difficult to achieve a House-Brackmann grade better than grade III. Outcomes are improving. Ultimately, the approach depends on the surgeon's experience.
Keywords: facial paralysis; dynamic rehabilitation; muscle transfer